2022
DOI: 10.1111/tmi.13796
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial biomarkers as predictors for haemodialysis need in severe leptospirosis patients (Weil's disease)

Abstract: Objective: To investigate the prediction ability of vascular injury biomarkers for haemodialysis requirement in patients with severe leptospirosis. Methods: Prospective study with severe leptospirosis patients hospitalised in Fortaleza, Brazil. Blood samples were collected hospital admission to quantify vascular injury biomarkers: syndecan-1, ICAM-1, VCAM-1, angiopoietin-2 and FGF-23. Two groups were evaluated according to haemodialysis requirement during hospital stay. Results: Twenty-seven patients were incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Currently, the search for biomarkers to predict the need for RRT in patients with severe leptospirosis has been of interest in the region. Meneses et al [11], in a prospective study carried out in Brazil, reported that patients with RRT presented significantly higher levels of Syndecan-1, angiopoietin-2, and FGF-23 compared to those without RRT. However, scientific progress is awaited to obtain more information on the use of these biomarkers in patients with severe leptospirosis.…”
Section: Renal Replacement Therapymentioning
confidence: 99%
See 4 more Smart Citations
“…Currently, the search for biomarkers to predict the need for RRT in patients with severe leptospirosis has been of interest in the region. Meneses et al [11], in a prospective study carried out in Brazil, reported that patients with RRT presented significantly higher levels of Syndecan-1, angiopoietin-2, and FGF-23 compared to those without RRT. However, scientific progress is awaited to obtain more information on the use of these biomarkers in patients with severe leptospirosis.…”
Section: Renal Replacement Therapymentioning
confidence: 99%
“…in the kidney involves the increased expression of proinflammatory molecules such as neutrophil gelatinase-associated lipocalin (NGAL), monocyte chemotactic protein 1 (MCP-1) [66], kidney injury molecule 1 (KIM-1), and N-acetyl-D-glucosaminidase (NAG) [67]. Although these biomarkers are not specific for AKI and leptospirosis, their measurement has been important in the early detection of AKI to reduce associated complications in patients with leptospirosis [11].…”
Section: Diagnosismentioning
confidence: 99%
See 3 more Smart Citations